The Impact of Digital Literacyon Fintech Service Usage Through Financial Literacy - Mulyono, Mulyono (E3S web of conferences, 2023)
The Covid-19 pandemic and lockdown have accelerated the pace of digital technology adoption and fintech services usage. Digital and financial literacy are needed to support the development of fintech services. This research proposes to study the influence of digital literacy on fintech services usage through financial literacy on college students. The data were collected through a questionnaire filled out by 165 respondents consisting of undergraduate students and postgraduate students and processed using SmartPLS statistics software. The variables used are digital literacy, financial literacy, and fintech service usage, and a moderator variable is education level. The result of the study is that the influence of digital literacy on fintech services usage through financial literacy is positive and significant. Similarly, the effect of digital literacy on financial technology usage moderated by education level is positive and significant. Therefore, introducing digital literacy and financial literacy in class subjects is needed so the students can take optimal benefits from the development of fintech.